Alumina nanoparticle filled epoxy resin: High strain rate compressive behavior. Issue 12 (17th January 2014) - Naik, N.K.; Pandya, Kedar S.; Kavala, V.R.; Zhang, W.; Koratkar, N.A.
<x xml:space="preserve">Abstract</x> This study demonstrates high strain rate behavior of neat epoxy and epoxy resin reinforced with 2 wt% and 5 wt% alumina nanoparticles. The present study investigates effect of strain rate as well as effect of alumina nanoparticle dispersion on the compressive stress – compressive strain behavior of epoxy resin. Studies were carried out on compressive split Hopkinson pressure bar apparatus in the strain rate range of 700–3200 per sec. Significant enhancement of compressive strength of epoxy resin up to 147% was noted at high strain rate compared with that at quasi‐static loading. The corresponding increase for alumina nanoparticle filled epoxy resin was up to 142%. It was also observed that the compressive strength of epoxy resin increases up to 8.6% with the addition of alumina nanoparticles at a strain rate of 3000 per sec. Synthesis of alumina nanoparticle filled epoxy resin, high strain rate and quasi‐static testing and main findings of the study are presented in this article. POLYM. ENG. SCI., 54:2896–2901, 2014. © 2014 Society of Plastics Engineers